High energy storage and colossal permittivity CdCu3Ti4O12 oxide ceramics. Issue 3 (1st February 2022) - Peng, Zhanhui; Wang, Jitong; Zhang, Fudong; Xu, Shudong; Lei, Xiaoping; Liang, Pengfei; Wei, Lingling; Wu, Di; Chao, Xiaolian; Yang, Zupei
Abstract: How to simultaneously realize colossal permittivity and high energy storage density has always been an urgent problem to be solved for ACu3 Ti4 O12 -family ( A C T O ) oxide materials. In this work, an effective strategy of enhancing breakdown field strength ( E b ) was adopted to achieve high energy storage density ( W ) in CdCu3 Ti4 O12 ( C d C T O ) ceramics via a semi-wet chemistry technique. Encouragingly, the E b of C d C T O oxide materials was enhanced obviously upon SiO2 doping, resulting in high energy storage density ( W ), maintaining high permittivity. Remarkably, at a SiO2 doping level of 4.0 w t %, a C d C T O - 4.0 w t % S i O 2 ceramic exhibited an enhanced energy storage density ( W ) of ∼1.77 mJ/cm 3 accompanied with a high E b of ∼2352 V/cm. Also, a good dielectric property with a high permittivity ε r of ∼5200 and a lowed loss tangent tan  δ of ∼0.06 at 10 kHz was obtained in C d C T O - 2.0 w t % S i O 2 ceramic. The acceptable dielectric properties and energy storage performances were ascribed to the significantly enhanced grain boundary resistance ( R g b ) due to the decreased grain size that formed upon SiO2 doping. Our findings in this work could provide useful insights as to how to simultaneously realize colossal permittivity and high energy storage density in C d C T O and other related dielectric ceramics. Graphical abstract: Image 1